Transparent Corneal Foreign Body - A Diagnostic Challenge in Children - Jitender Jinagal; Gaurav Gupta; Deepak Chandra Maurya; Jagat Ram (Delhi Journal of Ophthalmology)
A 5-years-old male, presented with unilateral itching, watering and photophobia, treated as allergic conjunctivitis elsewhere, with no improvement. On slit-lamp biomicroscopy, a shining reflex in superficial stroma was noted and anterior segment optical coherence tomography (AS-OCT) was suggestive of some foreign body (FB). On examination under anaesthesia, thin transparent plastic paper sheet FB was found and removed. Postoperatively, the FB impaction site was healed and replaced by a nebular corneal opacity. To conclude, careful examination as well as AS-OCT is helpful in detection of retained transparent intra-corneal foreign bodies especially in paediatric age group, in which history is not always reliable.